2007
DOI: 10.1063/1.2435357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diffusion on a time scale between nano- and milliseconds probed by field-cycling NMR relaxometry of intermolecular dipolar interactions: Application to polymer melts

Abstract: A formalism is presented permitting the evaluation of the relative mean-squared displacement of molecules from the intermolecular contribution to spin-lattice relaxation dispersion of dipolar coupled spins. The only condition for the applicability is the subdiffusive power law character of the time dependence of the mean-squared displacement as it is typical for the chain mode regime in polymer liquids. Using field-cycling NMR relaxometry, an effective diffusion time range from nano- to almost milliseconds can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
125
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(141 citation statements)
references
References 17 publications
11
125
0
Order By: Relevance
“…Indeed, as anticipated above, it has been shown that the intermolecular contribution to R 1 (ω) must not be ignored suggesting that the exponent α might also be influenced by the intermolecular relaxation [13,16,17,25]. Moreover, the intermolecular relaxation is an important source of information regarding translational dynamics in polymer melts.…”
Section: Full Dipolar Correlation Function In Polymer Meltsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, as anticipated above, it has been shown that the intermolecular contribution to R 1 (ω) must not be ignored suggesting that the exponent α might also be influenced by the intermolecular relaxation [13,16,17,25]. Moreover, the intermolecular relaxation is an important source of information regarding translational dynamics in polymer melts.…”
Section: Full Dipolar Correlation Function In Polymer Meltsmentioning
confidence: 99%
“…The next step of analysis of (8) is the approximation of the propagator by a Gaussian distribution [16,21]: …”
Section: Intermolecular Relaxation Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noteworthy in the present context that coherent neutron scattering which probes displacements of different scattering centers relative to each other has also an NMR analogue in a sense: evaluating the intermolecular dipolar interaction contribution to spin-lattice relaxation permits one to study relative diffusive displacements as demonstrated in Ref. 20. Thus, both the "self" and "pair" correlation functions of incoherent and coherent neutron scattering, respectively, have NMR counterparts which should be considered in any study of translational fluctuations.…”
mentioning
confidence: 99%
“…Numerous experimental NMR data on linear exible polymers (rubbers and thermoplastics) show that, in the amorphous state at T > T g (T g is the glass transition temperature), the FID is exponential for short chains with a average molecular weight M w < 10 4 and not exponential for longer chains M w > 10 4 [4]. And, irrespective of chemical structure of the polymer, the experimental dependence of the spin-spin relaxation time T 2 on the molecular weight M w and temperature shows that T 2 decreases with an increase in M w and at high temperature region has two clearly pronounced breaks [4].…”
Section: Introductionmentioning
confidence: 99%